Distribution, evolution, and diversity of retrotransposons at the flamenco locus reflect the regulatory properties of piRNA clusters. - Zanni, V.; Eymery, A.; Coiffet, M.; Zytnicki, M.; Luyten, I.; Quesneville, H.; Vaury, C.; Jensen, S. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Most of our understanding of Drosophila heterochromatin structure and evolution has come from the annotation of heterochromatin from the isogenic y; cn bw sp strain. However, almost nothing is known about the heterochromatin's structural dynamics and evolution. Here, we focus on a 180-kb heterochromatic locus producing Piwi-interacting RNAs (piRNA cluster), the flamenco (flam) locus, known to be responsible for the control of at least three transposable elements (TEs). We report its detailed structure in three different Drosophila lines chosen according to their capacity to repress or not to repress the expression of two retrotransposons named ZAM and Idefix, and we show that they display high structural diversity. Numerous rearrangements due to homologous and nonhomologous recombination, deletions and segmental duplications, and loss and gain of TEs are diverse sources of active genomic variation at this locus. Notably, we evidence a correlation between the presence of ZAM and Idefix in this piRNA cluster and their silencing. They are absent from flam in the strain where they are derepressed. We show that, unexpectedly, more than half of the flam locus results from recent TE insertions and that most of the elements concerned are prone to horizontal transfer between species of the melanogaster subgroup. We build a model showing how such high and constant dynamics of a piRNA master locus open the way to continual emergence of new patterns of piRNA biogenesis leading to changes in the level of transposition control.